10 movie western pack. Vol. 2 - Taylor, Buck, 1938-; Lancaster, Burt, 1913-1994.; Cooper, Chris; Parsons, Estelle; Lewis, Geoffrey, 1935-; Baldwin, Daniel, 1961-; Skogland, Kari.; Manduke, Joseph; Wheeler, Anne, 1946-; Totten, Robert, 1937-1995.; Petrie, Daniel; Petroni, Giulio; et al. ([United States] : Echo Bridge Home Entertainment, 2011)
Nothing too good for a cowboy: A group of young adults struggle to run the biggest cattle ranch in the world amidst World War II. Kid vengeance: Distraught by the murder of his parents and the kidnapping of his sister, a teenaged boy enlists the help of a gunslinger to seek revenge. Cowboys don't cry: A father and son struggle to make ends meet on the rodeo circuit. Pony Express rider: A young man joins the Pony Express mail service to track his father's killer. The gun and the pulpit: A quick-witted gunslinger flees his own hanging and poses as a traveling preacher is discovered dead int the desert. Death rides a horse: Bill--a witness to the robbery and murder of his parents when he was just a boy--embarks on a quest to hunt down the gang responsible. God's gun: When one of a pair of twin brothers is viciously gunned down, a gang is given free reign until the surviving brother takes justice into his own hands. Ned blessing: a haggard cowboy reflects upon his life while awaiting his death. Against a crooked sky: A young boy journeys into a harsh, unforgiving land to save his kidnapped sister. Vengeance Valley: This Westernized depiction of "Cain and Abel" is the gripping story of the complicated and volatile relationship between brothers.
Nothing too good for a cowboy (92 min.) (TV 1998) / writers, David Barlow, Charles Lazer ; director, Kari Skogland ; Kid vengeance (90 min.) (1977) / director, Joe Manduke ; Cowboys don't cry (103 min.) (1988) / writer/director, Anne Wheeler ; Pony Express rider (96 min.) (1976) / writers, Dan Greer, Hal Harrison Jr., Robert Totten ; director, Robert Totten ; The gun and the pulpit (74 min.) (TV 1974) / director, Daniel Petrie ; Death rides a horse (114 min.) (1967) / director, Giulio Petroni ; God's gun (94 min.) (1977) / director, Frank Kramer ; Ned blessing (94 min.) (TV 1992) / writer, Bill Wittliff ; director, Peter Werner ; Against a crooked sky (87 min.) (1975) / writers, Douglas Stewart, Eleanor Lamb ; director, Earl Bellamy ; Vengeance Valley (82 min.) (1951) / director, Richard Thorpe.
Buck Taylor, Burt Lancaster, Chris Cooper, Daniel Baldwin, Estelle Parsons, Geoffrey Lewis, Glynnis O'Connor, Jack Elam, Jack Palance, Jim Brown, Joanne Dru, John Ireland, John Phillip Law, Luis Avalos, Pamela Sue Martin, Rene Auberjonois, Richard Boone, Robert Lipton, Sarah Chalke, Slim Pickens, Leif Garrett, Ryan Gosling.
Rating: G.
DVD.
Keywords: Feature films; Western films